ESTUDO SOBRE O ESTÁGIO CURRICULAR PROFISSIONAL NOS CURSOS DA ÁREA TECNOLÓGICA DA UFF - Machado, Luiz Flávio Maia (2008)
This work refers to the professional internships in the Degree Programs of the Technological Center - CTC Fluminense Federal University - UFF. Initially a conceptual teaching-learning reflection concerning the management of knowledge is presented, followed by data and considerations about the environment and the situation of internships in the various engineering, architecture and computer science programs. The contribution as a supplement to the academic education is analyzed. The intent is to identify how to improve the effectiveness of internships as a professional training. Quantitative data gathered allows the observation of behaviors and trends of internships at the CTC, by examining causes and effects. Qualitative data collected in surveys done among the interns provides an analysis of the pedagogical, legal and managerial requirements of internships, as well as their motivations, deviations and results in accordance with those who had participated in internships and those who had coordinated them. The subject of this research had its focus upon the managerial concerns related to the professional internships as part of the undergraduate degree in the technological field. The intent was to investigate a typical managerial educational query, which still has been barely explored within the Brazilian College Institutions. In order to deepen the subject in the given research, the descriptive assessment method was employed, which is based on the observation of facts and data of actual situations. The research evolves upon the verification of the pertinent understanding and interpretation confronted by reality awareness, which is characterized, nowadays, by the competitive job market. Within the scope, this research embraces originality and is intended to constitute a reference to those interested in the concerns of the professional internships and also to guide an adequate Internship Managerial System, in connection with the actual data of current scenarios.